2017
DOI: 10.1038/s41598-017-16252-1
|View full text |Cite
|
Sign up to set email alerts
|

Speeding up bioproduction of selenium nanoparticles by using Vibrio natriegens as microbial factory

Abstract: Selenium and selenium nanoparticles (SeNPs) are extensively used in biomedicine, electronics and some other industrial applications. The bioproduction of SeNPs is gaining interest as a green method to manufacture these biotechnologically relevant products. Several microorganisms have been used for the production of SeNPs either under aerobic or anaerobic conditions. Vibrio natriegens is a non-pathogenic fast-growing bacterium, easily cultured in different carbon sources and that has recently been engineered fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 66 publications
7
57
1
1
Order By: Relevance
“…These pathways, cloned from three different bacteria, did not need to be codon optimized for expression in V. natriegens. Overall, this first demonstration of heterologous natural product production using these different carbon sources serves to further develop the biotechnological usefulness of this organism, which has also been investigated for production of alanine, poly-ß-hydroxybutyrate, and selenium nanoparticles, all using native genes [5,7,73]. We anticipate that these results will encourage future efforts at optimizing bioproduction of other complex natural products in this chassis.…”
Section: Heterologous Production Of Violaceinmentioning
confidence: 81%
“…These pathways, cloned from three different bacteria, did not need to be codon optimized for expression in V. natriegens. Overall, this first demonstration of heterologous natural product production using these different carbon sources serves to further develop the biotechnological usefulness of this organism, which has also been investigated for production of alanine, poly-ß-hydroxybutyrate, and selenium nanoparticles, all using native genes [5,7,73]. We anticipate that these results will encourage future efforts at optimizing bioproduction of other complex natural products in this chassis.…”
Section: Heterologous Production Of Violaceinmentioning
confidence: 81%
“…Briefly, acidified KMnO 4 solution (0.630 mM, 10 ml) was prepared in 0.5 M H 2 SO 4 . Simultaneously, ascorbic acid standard solutions of varying concentrations (1,4,8,12,16, and 20 μg ml −1 ) were also prepared. Then, 0.1 ml of KMnO 4 was added to 1 ml of ascorbic acid solutions and incubated at room temperature for 5 min.…”
Section: Estimation Of Ascorbic Acid Content In Ig Extractmentioning
confidence: 99%
“…It also forms an essential component of selenoproteins that are required for antioxidant activities such as protection of DNA from oxidative stress [15]. Several studies have demonstrated that nSe exhibit size dependent biological activities [14,16]. For instance, the capability of nSe to scavenge free radicals enhances as the particle size decreases, thereby preventing oxidative stress efficiently compared to the larger particles [15,17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the shortest doubling time of all known organisms, Vibrio natriegens has garnered considerable interest as a promising microbial host to accelerate research and biotechnology [1][2][3][4] . Its rapid growth rate, which has been linked to high rates of protein synthesis 5 and metabolic efficiency 6,7 suggests that this host may be harnessed as a powerful cell-free expression system.…”
mentioning
confidence: 99%